2010
DOI: 10.1016/j.lungcan.2009.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Limited thymectomy for stage I or II thymomas

Abstract: Resection of thymomas with surrounding tissue instead of total thymectomy can be indicated for stage I or II thymomas in light of disease free and overall survival, post-operative onset of MG, and the incidence of multiple lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 25 publications
4
49
0
Order By: Relevance
“…Ito et al (18) reported that the incidence of postoperative MG was 5.0% in the thymectomy group and 4.2% in the thymomectomy group, with no significant difference between the two groups. Similar results were reported by Tseng et al (3) and Onuki et al (2). In the present study, only two patients (0.81%) without preoperative MG developed MG after surgery, both in the thymectomy group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Ito et al (18) reported that the incidence of postoperative MG was 5.0% in the thymectomy group and 4.2% in the thymomectomy group, with no significant difference between the two groups. Similar results were reported by Tseng et al (3) and Onuki et al (2). In the present study, only two patients (0.81%) without preoperative MG developed MG after surgery, both in the thymectomy group.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is no consensus on the appropriate extent of thymic resection (2)(3)(4). Although thymectomy may help prevent potential risks of postoperative myasthenia gravis (MG) and intrathymic or locoregional recurrence (5,6), some consider that tumor resection alone (thymomectomy) may be enough for noninvasive thymomas without MG (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the prognosis of the patients with early-staged thymoma has been extremely good, limited thymectomy may be utilized. Onuki et al reported the efficacy of limited thymectomy for stage I or II thymomas (15). If the tumor invasion to the surrounding organs is apparent intraoperatively, we should convert the operative procedures from limited thymectomy to extended or total thymectomy.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the paper entitled "Limited thymectomy for stage I and II thymomas" [1]. The ideal treatment for patients with thymoma is still debated; however, most of the discussion is dedicated to advanced stage lesions [2].…”
Section: Surgical Treatment Of Early Stage Thymomamentioning
confidence: 99%